The The Effect of Financial Literacy and Financial Technology Payment on Financial Management of Students Using Paylater - Emiliyana, Fitri; Safitri, Teti Anggita (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction: An economic business entity with a balance of trade-offs between maximizing profit (Juhari et al., 2022). The ability to adapt the need of uncomfortable changes and uncertain condition (Diharto, 2018). The more advanced technology and competition, the better it is to search for need (Hidayat et al., 2023). The development of increasingly advanced technology, in the form of the internet, makes it possible for information to be accessed from various places (Anita et al., (2019).Improving the quality of human resources regarding the renewal of effective and efficient administrative governance through non-formal education (Aji et al., 2022). Communication has an important role in creating or realizing the duality of structuration (Rasyid, 2022). Utilize information technology and communication to support effectiveness and administrative efficiency ( Aji et al., 2022). Students often experience financial problems, one of which is caused by consumptive behavior. Extends to a broader transdisciplinary interest (Boro, 2023). Most of the students make online transactions or online loans through fintech payments (Paylater), and they think that using Paylater can help solve their financial problems and needs. Crashes and high expectations in certain conditions will result in a financial crisis (Sumar’in et al., 2020). Given this, financial management requires an understanding of and knowledge of financial literacy and fintech payments (PayLater). The problem faced is not bookkeeping money ( Diyah et al., 2020). Understand and have limited access to obtain capital assistancefrom financial institutions (Hafni et al., 2020). Purpose: This study aims to determine whether there is an effect of financial literacy and fintech payments (PayLater) on student financial management. Methodology/Approach: This research is a type of quantitative research with an associative strategy. As the largest Muslim country in the world, Indonesia is a home to many Islamic organizations whose activities are as diverse as their religious orientation (Samsudin, 2022).The sample used is active students at Aisyiyah Yogyakarta University who use one of the paylater types (Shopee Paylater, GoPayLater, Kredivo, Akulaku, and Traveloka Later). The data collection method in this study used primary data collected by distributing questionnaires online to all students at Aisyiyah University, Yogyakarta. Findings: The results obtained after data analysis are that partially financial literacy (X1) has a significant effect on the financial management of students using paylater (Y), while financial technology payments (X2) have no effect on the financial management of students using paylater (Y). Simultaneously, financial literacy (X1) and financial technology payments (X2) affect the financial management of pay-later-using students at 'Aisyiyah University, Yogyakarta. Originality/ Value/ Implication: The results of this study can be concluded as follows: 1) There is a significant simultaneous effect on financial literacy (X1) and financial technology payments (X2) on the financial management of students who use paylater. 2) There is a significant partial effect of financial literacy (X1) on the financial management of students who use paylater. and 3) There is no effect of financial technology payments (X2) on the financial management of students using paylater.